The Use of the Fun English Learning (FEL) Application in Enhancing Students’ English Vocabulary - Hasprilia Putri Shafira; Ibrahim Manda; Andi Sadapotto; Buhari; Sam Hermansyah (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
This study examined the effectiveness of the Fun English Learning (FEL) application in enhancing the English vocabulary mastery of eighth-grade students at UPT SMP Negeri 1 Pangsid, Sidenreng Rappang. A quantitative quasi-experimental method with a pre-test-post-test control group design was employed. The participants consisted of 31 students: 16 students in the experimental group who learned vocabulary through the FEL application and 15 students in the control group who received conventional instruction. A 20-item multiple-choice vocabulary test was administered before and after the treatment. The data were analyzed using descriptive statistics, the Shapiro-Wilk test, Levene's test, and an Independent Samples t-test with SPSS version 26. The experimental group's mean score increased from 63.13 on the pre-test to 77.19 on the post-test, whereas the control group's mean score changed only from 58.00 to 58.67. The post-test comparison yielded t(29) = 5.007, p < 0.001, with a mean difference of 18.52 points. The findings demonstrate that students taught through FEL achieved significantly higher vocabulary outcomes than students taught through conventional instruction. The application's interactive games, quizzes, pronunciation practice, listening activities, multimedia support, and immediate feedback provided repeated and engaging opportunities to process vocabulary. Therefore, FEL can be considered an effective technology-assisted medium for supporting vocabulary instruction among junior high school students.